Jual Beli Hewan Qurban dan Aqiqah Berbasis Android Menggunakan Metode UCD - Sukri; Muhammad Irham; Untung Santosa Gea; Weli Andrian (JEKIN - Jurnal Teknik Informatika, 2025)
Abstract-M-commerce is a transaction carried out in a wireless scope, using a mobile phone to access the internet and shop which can be done anywhere and anytime. The purpose of this study is to facilitate Sellers (farmers) and buyers and provide convenience in Kampar Kiri in making transactions. Data collection was carried out through literature studies, interviews, and observations. Quantitative methods were used in the research process, especially in the testing stage. The Qurqah application was built with the help of User-Centered Design (UCD) so that it has a high usability value, and uses Firebase as a place to store data. The Qurqah application was tested using black box testing which was successful, and tested through the User Acceptance Test (UAT) by obtaining an average value of 92.8% from 5 sellers and 95.44% from 25 buyers (the public), which was categorized in the predicate "Very Good", indicating the satisfaction of sellers and buyers with the Qurqah application. The results of this study prove that the Android-based Qurqah application can facilitate sales and is able to increase livestock sales results.